HUBUNGAN ANTARA VERBAL ABUSE ORANGTUA DENGAN PERILAKU AGRESIF PADA REMAJA DI SMAN 14 KABUPATEN TANGERANG - Sapitri, Imas (Nusantara Hasana Berdikari, 2021)
Verbal violence is violence such as bullying, referring to children, ridiculing, embarrassing, berating and frightening using harsh words (Indrayati & Ph, 2019). Violence through words can arise when the mother is busy and her child asks for attention but the mother is silent or even utters harsh words such as naughty, stupid, fussy, annoying, and other harsh words that can offend the child. It is these words that will always be remembered by children, if they are spoken continuously (Telaumbanua, 2017). Research Objectives: To determine the relationship between parental verbal abuse and aggressive behavior in adolescents at SMAN 14 Tangerang district in 2021. Research Methods: This study was a quantitative study with a quantitative research design with a descriptive method. The population of this study were adolescents aged 16-17 years, the sampling technique used total sampling with a total sample of 97 respondents. The instrument used is a questionnaire sheet containing several questions. The data analysis technique used univariate analysis. Research results : Based on bivariate analysis using chi-square that p-value 0.000 <0.05, it can be concluded that Ha is accepted and Ho is rejected so that it can be concluded that there is a significant relationship between parental verbal abuse and aggressive behavior in adolescents at SMAN 14 Kab. . Tangerang. Conclusion: There is a relationship between the level of knowledge of eating patterns with risk factors for Diabetes Militus at SMAN 14 Tangerang district in 2021. Suggestion: It is hoped that it can be useful for readers.